Joubert Syndrome in French Canadians and Identification of Mutations in CEP104 - Srour, Myriam; Hamdan, Fadi F.; McKnight, Dianalee; Davis, Erica; Mandel, Hanna; Schwartzentruber, Jeremy; Martin, Brissa; Patry, Lysanne; Nassif, Christina; Dionne-Laporte, Alexandre; Ospina, Luis H.; Lemyre, Emmanuelle; et al. (American journal of human genetics, 2015)
Joubert syndrome (JBTS) is a primarily autosomal-recessive disorder characterized by a distinctive mid-hindbrain and cerebellar malformation, oculomotor apraxia, irregular breathing, developmental delay, and ataxia. JBTS is a genetically heterogeneous ciliopathy. We sought to characterize the genetic landscape associated with JBTS in the French Canadian (FC) population. We studied 43 FC JBTS subjects from 35 families by combining targeted and exome sequencing. We identified pathogenic (n = 32 families) or possibly pathogenic (n = 2 families) variants in genes previously associated with JBTS in all of these subjects, except for one. In the latter case, we found a homozygous splice-site mutation (c.735+2T>C) in CEP104. Interestingly, we identified two additional non-FC JBTS subjects with mutations in CEP104; one of these subjects harbors a maternally inherited nonsense mutation (c.496C>T [p.Arg166∗]) and a de novo splice-site mutation (c.2572−2A>G), whereas the other bears a homozygous frameshift mutation (c.1328_1329insT [p.Tyr444fs∗3]) in CEP104. Previous studies have shown that CEP104 moves from the mother centriole to the tip of the primary cilium during ciliogenesis. Knockdown of CEP104 in retinal pigment epithelial (RPE1) cells resulted in severe defects in ciliogenesis. These observations suggest that CEP104 acts early during cilia formation by regulating the conversion of the mother centriole into the cilia basal body. We conclude that disruption of CEP104 causes JBTS. Our study also reveals that the cause of JBTS has been elucidated in the great majority of our FC subjects (33/35 [94%] families), even though JBTS shows substantial locus and allelic heterogeneity in this population.